HISTORICAL DEVELOPMENT OF CARDIAC SURGERY (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article presents a comprehensive historical overview of the development of cardiac surgery, from its early experimental stages to modern high-technology interventions. It traces key global milestones—beginning with pioneering operations by Daniel Hale Williams and Ludwig Rehn—and highlights groundbreaking innovations such as the heart-lung machine, heart transplantation, and minimally invasive surgical techniques. Special attention is given to the evolution of cardiac surgery in Uzbekistan, profiling leading national specialists and institutions that have contributed to the field's regional development. The article underscores the collaborative, international nature of cardiac surgery and its continuing advancement through scientific research, technological innovation, and strategic healthcare investment.